2004
DOI: 10.1007/s00296-004-0438-0
|View full text |Cite
|
Sign up to set email alerts
|

Lp(a) lipoprotein and lipids in patients with rheumatoid arthritis: serum levels and relationship to inflammation

Abstract: It is suggested that higher serum Lp(a), lower HDL-C, higher TG level, and a high ratio of TC/HDL-C might show high risk of atherosclerosis. Inflammation in RA may cause changes in HDL-C and Lp(a) metabolisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
75
1
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(104 citation statements)
references
References 28 publications
16
75
1
10
Order By: Relevance
“…27 In this study we found that patients diagnosed with RA had significantly reduced levels of HDLcholesterol in comparison to control groups. This matched with many other studies done in all of Pakistan 2012, 25 Tunisia 2011, 26 Malaysia 2012, 28 South India, 29 Saudi Arabia 2013, 30 Baghdad, Iraq 2013 31 and the United Kingdom 2011, 32 which is an unfavorable profile about cardiovascular risks 33 and there was no study against it. In this study, we found that there was a statistically significant elevation in all of the serum triglycerideable 2, serum Dyslipidemia has a higher significant prevalence among RA patients in comparison to control groups.…”
Section: P Value Discussionsupporting
confidence: 50%
“…27 In this study we found that patients diagnosed with RA had significantly reduced levels of HDLcholesterol in comparison to control groups. This matched with many other studies done in all of Pakistan 2012, 25 Tunisia 2011, 26 Malaysia 2012, 28 South India, 29 Saudi Arabia 2013, 30 Baghdad, Iraq 2013 31 and the United Kingdom 2011, 32 which is an unfavorable profile about cardiovascular risks 33 and there was no study against it. In this study, we found that there was a statistically significant elevation in all of the serum triglycerideable 2, serum Dyslipidemia has a higher significant prevalence among RA patients in comparison to control groups.…”
Section: P Value Discussionsupporting
confidence: 50%
“…With respect to Lp(a), although there have been numerous reports of elevated levels during acute and chronic inflammation (30), studies examining changes in the level of Lp(a) in association with suppression of inflammation are lacking. Although a recent meta-analysis suggested that Lp(a) is independently associated with an elevated risk of CHD (31), whether Lp(a) is causally linked to CHD is not known.…”
mentioning
confidence: 99%
“…Insulin resistance was observed due to an alleged increase in oxidative stress as well as over expression of pro-inflammatory cytokines [40].…”
Section: Metabolic Abnormalitiesmentioning
confidence: 99%